'Ci sono troie in giro in Parlamento che farebbero di tutto': Italian female politicians seen through a sexual lens. (29th December 2016) - Formato, Federica
Abstract : Italian female politicians are increasingly gaining access to the institutional public space, in some cases breaking the glass ceiling that has blocked them from reaching high positions. However, language used to attack them for their possible wrong doings or employed to represent themselves demonstrates that a rearrangement of a gendered xed order is constantly challenged by (those in) a culture and society that still sees women as mainly pertaining to the private sphere. In this article, I qualitatively investigate sexual terms, directly and indirectly sexist, used by a variety of actors (journalists, comedians, politicians) attempting to prove women's unsuitability for political roles and, more broadly, for operating in the institutional public sphere. To examine these terms, I developed a framework which takes into consideration communicative functions (stereotypes, gossip and self-representation), aimed at providing a comprehensive and context-dependent investigation into how language is purposefully used to re-establish a known gendered structure (only men in the institutional sphere). Nexus analysis, borrowed from anthropologists Ron Scollon and Suzanne Scollon, is here performed in order to show how language is intrinsically linked to an ideologically gendered order which speakers seem to reproduce through linguistic practices. This article contributes to previous literature on Italy as a highly sexist culture as well as that on representation of female professionals operating in domains which have been historically inhabited by men. It also offers a methodological tool to investigate sexist terms employed in the media and in political spaces.